Renal Lymphoma: Primary or First Manifestation of Aggressive Pediatric B‑cell Lymphoma - Coca, Pragnya; Linga, Vijay; Gundeti, Sadashivudu; Tandon, Ashwani (Indian Journal of Medical and Paediatric Oncology, 2017)
Renal lymphoma is an uncommon renal tumor in children. Unlike renal lymphomas presenting as bilateral disease and renal failure, we report a boy who presented with unilateral renal involvement. After initial nephrectomy, he achieved remission with multiagent chemotherapy but relapsed systemically within 3 months. He was initiated on salvage chemotherapy with autologous bone marrow transplant. Even though the initial manifestation was localized lymphoma eventually, it turned out to be a systemic disease. He succumbed to disease at 14 months from diagnosis.
Keywords: Chemotherapy; nephrectomy; renal lymphoma